LITERATURE REVIEW ON ANTI-DRONE TECHNOLOGY AND DEFENSE SYSTEMS - bayuhartono; Hartono, Bayu; Saputro, Guntur; Rukmono, Linus (Jurusan Teknologi Informasi Universitas Semarang, 2026)
Research on anti-drone technology and modern air defense systems is growing as the use of drones in military and civilian contexts increases. Major trends in development include the use of radar, optical sensors, microwave technology, and the integration of artificial intelligence (AI) to improve detection speed and accuracy. Recent studies show that combining several technologies can improve drone identification accuracy. The research methods used are diverse, such as computer simulations, field tests, and cost-benefit analyses. The results of the research reveal that there are still challenges, including detection errors, slow responses, and limited range. In addition, ethical and legal aspects are also important considerations. Overall, this review provides a comprehensive overview of the latest developments and challenges in the implementation of anti-drone technology.